IMPLEMENTASI DISCOVERY LEARNING BERBANTUAN GEOGEBRA DAN DESMOS UNTUK MENINGKATKAN KEMAMPUAN PENALARAN MATEMATIS - Atsila Rahmani; Rostina Sundayana; Nova Nurhanifah (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
Mathematics is a discipline that is abstract, logical, systematic, and characterized by strong interconnections between concepts. This abstract nature often causes students to experience difficulty in developing mathematical reasoning abilities as well as building self-directed learning. Therefore, appropriate learning models and media are required to help students actively construct knowledge and visualize mathematical concepts. The Discovery Learning model, supported by instructional technologies such as GeoGebra and Desmos, is capable of facilitating the concept discovery process and dynamically visualizing mathematical objects. This study aims to analyze the differences in the improvement of students' mathematical reasoning abilities and self-directed learning between students who were taught using the GeoGebra -assisted Discovery Learning model and those using Desmos. The research method used was a quasi-experiment with a Nonequivalent Pretest–Posttest Group Design. The study population consisted of 12th-grade students at SMA Negeri 6 Garut. Data analysis techniques included the normalized gain (N-Gain) test and the Mann–Whitney test. The results showed that the mathematical reasoning ability of students receiving GeoGebra -assisted Discovery Learning was better than that of students receiving Desmos-assisted Discovery Learning , with average N-Gain scores of 0,51 and 0,30, respectively, both in the moderate category. Keywords: Discovery Learning , GeoGebra , Desmos, Mathematical Reasoning Ability